2016
DOI: 10.21767/2471-3082.100009
|View full text |Cite
|
Sign up to set email alerts
|

Axial Contour Alteration following Restorative Treatment: A Systematic Review

Abstract: Purpose: This qualitative systematic review had two aims: (1) evaluation of the impact of restorative treatment on tooth contour, and (2) investigation of the effect of altered tooth contour on biological health.Methods: An electronic search was conducted using PubMed (MEDLINE), Cochrane Library and Google Scholar. A combination of relevant key words was applied. The search was completed in October 2015 and was confined to peer-reviewed studies published in English. Results:The initial search had disclosed a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Selection of a reference standard tooth is an arbitrary institutional decision, and for purposes of this study, we selected the typodont tooth as having representative morphologic contours, adequately representing those that would function harmoniously in the virtual patient "mouth." [7][8][9][10][11][12][15][16][17][18][19][20][21][22] Using individual aspect clinical data to reine the tolerance to ±0.38 mm allows a single value to be applied to the entire surface, which simpliies the digital grading worklow. Initially, we uniformly applied a ±0.50 mm surface contour tolerance comparable to that reported by McPherson et al to each aspect of the tooth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection of a reference standard tooth is an arbitrary institutional decision, and for purposes of this study, we selected the typodont tooth as having representative morphologic contours, adequately representing those that would function harmoniously in the virtual patient "mouth." [7][8][9][10][11][12][15][16][17][18][19][20][21][22] Using individual aspect clinical data to reine the tolerance to ±0.38 mm allows a single value to be applied to the entire surface, which simpliies the digital grading worklow. Initially, we uniformly applied a ±0.50 mm surface contour tolerance comparable to that reported by McPherson et al to each aspect of the tooth.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Each of the deined surface contours of the reference tooth (mesial proximal, distal proximal, facial axial, lingual axial, and occlusal) was digitally segmented, and the total surface area in each segment was computed using Autodesk Meshmixer (www.meshmixer.com; Figure 1). This tolerance was subsequently reined to ±0.38 mm following a survey of peer-reviewed literature to determine clinically acceptable thresholds that, if exceeded, would lead to biological or biomechanical morbidities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tolerance was derived from peer-reviewed clinical literature, considering clinically acceptable thresholds for morphologic contour deviation by surface, before biological or biomechanical morbidities are observed to occur. [7][8][9][10][11][12] For example, Abduo's systematic review noted little periodontal impact from axial surface over contour in the gingival third until a value of 0.50 mm was reached; at that point, an increase in plaque retention, gingivitis, and attachment loss was observed. 7 By contrast, that study found that occlusal surface variation was generally less accommodating, based on histological measurements of the periodontal ligament width, which ranges from approximately 0.15 mm on average at mid-root to 0.25 mm at root apex.…”
Section: Methodsmentioning
confidence: 99%
“…This could be explained by the fact that maxillary canines are difficult to prepare due to different morphology and line angles. In a review conducted by Abduo, 25 he concluded that axial contour alteration is inevitable after restorative treatment. The alterations were mainly in the form of increasing the contour, which appears to be associated with negative biological consequences.…”
Section: And Bl Dimensions Of Antimeric Natural Teeth and Cementedmentioning
confidence: 99%